1991
DOI: 10.1002/ajmg.1320410403
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal recessive ectodermal dysplasia: I. An undescribed dysplasia/malformation syndrome

Abstract: We describe 27 individuals of 7 families related to each other with high probability who showed manifestations of ectodermal dysplasia and other anomalies affecting females as severely as males with variable expressivity. All parents were normal. These families were detected in a relatively isolated and inbred population with very small neighbouring communities from a Caribbean Sea island, Margarita Island, in Northeastern Venezuela (Nueva Esparta State). The clinical picture common to all patients could not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 15 publications
1
29
0
Order By: Relevance
“…NECTIN-2 (PVRL1) codes for a cell adhesion molecule that is expressed in mouse tooth buds. Persons with ZlotogoraOgur syndrome (Zlotogora, 1994) or the Margarita Island form of ectodermal dysplasia (Bustos et al, 1991) caused by a PVRL1 mutation have syndactyly, cleft lip/palate, nail and hair dysplasia, and hypodontia. Hypodontia affects mainly the upper lateral incisors, and additionally the sizes and shapes of tooth crowns differ (Bustos et al, 1991).…”
Section: Genes Behind Syndromic Hypodontia and Their Significance In mentioning
confidence: 99%
“…NECTIN-2 (PVRL1) codes for a cell adhesion molecule that is expressed in mouse tooth buds. Persons with ZlotogoraOgur syndrome (Zlotogora, 1994) or the Margarita Island form of ectodermal dysplasia (Bustos et al, 1991) caused by a PVRL1 mutation have syndactyly, cleft lip/palate, nail and hair dysplasia, and hypodontia. Hypodontia affects mainly the upper lateral incisors, and additionally the sizes and shapes of tooth crowns differ (Bustos et al, 1991).…”
Section: Genes Behind Syndromic Hypodontia and Their Significance In mentioning
confidence: 99%
“…Coarse, dry, sparse, and extremely slowly growing hair is a characteristic feature of RHS, but it is also found in other ectodermal dysplasia with clefting syndromes such as EEC, 30-43 AEC, 5,45,53 and others. 44,52,[54][55][56][57] Hair color changes Of the reviewed RHS cases, hair color characteristics were mentioned in 16 cases. These were described as white, 16 hypopigmented, 8,25 light colored, 6,24,58 fair, 22 blondish white, 16 blondish, 16,17 ginger, 51 reddish, 16,26 and black.…”
Section: Trichologic Characteristicsmentioning
confidence: 99%
“…Autosomal recessive CL/P-ectodermal dysplasia syndrome (CLPED1, MIM 225000), previously called Margarita Island ectodermal dysplasia (MIM 225060), is characterized by CL/P, dental anomalies, hand anomalies, hidrotic ectodermal dysplasia, and occasionally mental retardation (Bustos et al 1991). Suzuki et al (2000) identified a nonsense mutation (G546A; W185X), a deletion (546delG), and a duplication (959dupG) of PVRL1, the poliovirus receptor like-1 gene at 11q23, in CLPED1 families from Margarita Island in north Venezuela, in patients from Israel, and patients from Brazil, respectively.…”
Section: Pvrl1mentioning
confidence: 99%